Some population genetics parameters of the present Hungarian Hucul Horse population - Mihók, Sándor; Somogyvári, Enikő; Posta, János (Acta Agraria Debreceniensis, 2016)
We examined the Hungarian population of the Hucul horse breed, under genetic protection, based on population genetic indicators until the year 2014 included. The evaluation was performed using the Endog programme based on the following indicators: inbreeding coefficient, average relatedness, the maximum number of generations, the number of full generations traced and offspring number. Our findings were as follows: the average inbreeding coefficient of the total population was 5.99%, average relatedness was 11.82%, the maximum number of generations was, on the average, 16.04%, and the number of full generations traced with reference to the whole population was 4.15% on the average. 40% of the whole population (723 individuals) did not have any offspring; 42% (759 individuals) attained an offspring of 1 or 2, while 3.4% (88 individuals) had a surviving offspring of 3. The highest offspring number according to the national database (92) was attained by one stallion.